Ethological control of Conotrachelus dubiae in camu-camu fruits [Myrciaria dubia (Kunth) H.B.K.] - Panduro, Mario Pinedo; bardales-lozano, Ricardo; vasquez-bardales, joel; Paredes-davila, Elvis; Abanto-rodriguez, Carlos; Durand-valencia, Jaime (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
The objective was to evaluate methods for the control of the weevil (Conotrachelus dubiae) of camu-camu (Myrciaria dubia) in a floodplain plot of a farmer near Iquitos, Loreto, Peru. Twenty-eight 6-year-old plants with similar architecture and branching were selected for the study. The treatments were: adhesive tape (T1), bottle with attractive food (T2), pegant yellow sheet (T3) and control (T4) with randomized complete block design (DBCA), 7 replicates and 1 plant per experimental unit. The total number of fruits (NTF), fruits attacked by weevil (FAG), fallen fruits (FC), fruits weight (PF) and fruit yield (RF) were evaluated. Significant differences were found between treatments for NTF, FAG and FC, and no differences were found for PF. The NTF for T1, T2, T3 and T4 were: 353, 280, 143 and 125 respectively. The highest RF values corresponded to T1 (3.03 kg / pl) and T2 (2.78 kg / pl). T1 caused the lowest values of FC(16%) and FAG (22.73%). Negative correlations were found between RF versus FAG (r = -0.57) and FC (-0.73). We conclude that the most effective control against C. dubiae is the application of the trap with adhesive tapes.